Frequency and Severity of Anemia in Pregnant Women at Gwadar Development Authority Hospital, Gwadar, Balochistan - Latif, Majid; Ayaz, Saeed Bin; Munir, Muhammad Usman; Rehman, Laeeq Ur; Anwar, Muhammad; Ishaq, Mansoor; Manzoor, Muneeba; Aamir, Muhammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency and severity of anemia among pregnant women and find association of anemia with age, number of pregnancies, and the trimester of pregnancy at Gwadar Development Authority (GDA) Hospital, Gwadar, Baluchistan.Study Design: A cross-sectional study.Place and Duration of Study: Gwadar Developmental Authority Hospital, Gwadar Pakistan, from Sep 2017 to Feb 2018.Methodology: Through consecutive sampling, we included 200 women diagnosed with pregnancy reporting for routine checkup. The samples were taken through antecubital veins using aseptic technique and the hemoglobin was analyzed using Medonic M-series M32 Hematology Analyzer. We used definitions of anemia given by the World Health Organization. The data were analyzed using SPSS version 20.Results: The mean age was 26.2 ± 5.6 years (range: 17-43 years). The mean hemoglobin was 10.1 ± 1.4 g/dL while the mean values for mean corpuscular volume and mean corpuscular hemoglobin were 70.5 ± 10.1 f Land 24.1 ± 4.2 pg respectively. The frequency of anemia was 73% (n=146). Most (40%, n=80) women had anemia of moderate intensity. Mild anemia was most prevalent in the first trimester while moderate and severe anemia was in the third trimester. No significant interactions of woman’s age, number of pregnancies, and the trimester of pregnancy were found with the presence of anemia.Conclusion: The frequency of anemia among pregnant women attending GDA hospital was 73% with maximum women having moderate anemia. Woman’s age, number of pregnancies, and the trimester of pregnancy did not have any significant association with anemia.